Enhancing Breastfeeding Self-Efficacy through Lactation Booklets among Mothers in Slateng, Ledokombo - Novita; Firdha Novitasari (Journal of Nursing Periodic, 2026)
Introduction: The optimal nourishment for infants is to nurse exclusively throughout the first six months of their lives. Nonetheless, many Indonesian mothers continue to struggle with exclusive breastfeeding. Objective. The objective of this study was to look into how lactation booklet delivery affected nursing self-efficacy among mothers in Slateng Village, Ledokombo District. Methods: The study employed a pre-experimental design using a one-group pretest-posttest model. The instrument used was the Indonesian Breastfeeding Self-Efficacy Scale-Short Form (BSE-SF). There were 69 breastfeeding mothers in Slateng Village, Ledokombo District. The Wilcoxon statistical test was employed to evaluate the data. Results: The intervention exhibited a large effect size (r = 0.87), indicating a significant favorable impact on breastfeeding self-efficacy. Keywords: Breastfeeding self-efficacy (BSE), BSE-SF, Exclusive breastfeeding.